Acculturation of Malay and Javanese Culture in Limas House Building Art: A Comparative Study of Limas Houses and Joglo Limasan Houses - Raihan Sulthan Al-Faris; Herwandi Herwandi (Mahesa Research Center (PT. Mahesa Global Publishing), 2024)
This research discusses acculturation between Javanese and Malay culture found in the traditional house of South Sumatra, namely Rumah Limas. This research uses historical research methods with a comparative descriptive perspective. When the Sriwijaya kingdom began to collapse in the 12th century, kingdoms from Java began to enter Palembang. After that, Raden Fatah founded the Demak Kingdom in Palembang which became the forerunner to the founding of the Palembang Darussalam Sultanate. A form of acculturation between Malay and Javanese culture is found in Rumah Limas which is a traditional house from South Sumatra. This acculturation is found in the roof shape of the Limas House which is adapted from the Limasan Joglo House, Central Java. Historically, this acculturation occurred because the Palembang Darussalam Kingdom was an Islamic kingdom in Palembang which had Javanese influences in its government structure.